PENGGUNAAN METODE BERMAIN PERAN DALAM PENINGKATAN HASIL PEMBELAJARAN IPS DI KELAS V SD NEGERI 14 SUNGAI SIRAH KECAMATAN SUTERA - nal, Ardi (Inovasi Pendidikan, 2017)
Learning by using the method of playing toto the role very well implemented to improve student learning outcomes, both in terms of creativity, cooperation within the group, problem solving and interaction in social life. By using this method, students were beginning tended to be active in learning. Moreover, by using the method of playing this role, the teacher will be awarded to students who obtain the highest value. Increased student learning outcomes can be seen from toto the average obtained in the first cycle ie 6.7 and increased in the second cycle which is 8.2. This is evidence of the successful implementation of the research toto that has been done in SDN 14 Sungai Sirah the District Sutera. Key words: role playing method, IPS